2013
DOI: 10.2140/apde.2013.6.1089
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization for the semilinear wave equation with geometric control condition

Abstract: In this article, we prove the exponential stabilization of the semilinear wave equation with a damping effective in a zone satisfying the geometric control condition only. The nonlinearity is assumed to be subcritical, defocusing and analytic. The main novelty compared to previous results, is the proof of a unique continuation result in large time for some undamped equation. The idea is to use an asymptotic smoothing effect proved by Hale and Raugel in the context of dynamical systems. Then, once the analytici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…This seems hard to prove for finite times, since the propagation of analytic microlocal regularity is often more complicated to obtain for nonlinear equations. To overcome this, in a forthcoming article with R. Joly [18], we prove such analyticity in time for a solution satisfying ∂ t u = 0 on R × ω with a subcritical analytic nonlinearity. This would then give some unique continuation result in infinite time, which is sufficient for stabilization.…”
Section: A Few Comments About Unique Continuationmentioning
confidence: 99%
“…This seems hard to prove for finite times, since the propagation of analytic microlocal regularity is often more complicated to obtain for nonlinear equations. To overcome this, in a forthcoming article with R. Joly [18], we prove such analyticity in time for a solution satisfying ∂ t u = 0 on R × ω with a subcritical analytic nonlinearity. This would then give some unique continuation result in infinite time, which is sufficient for stabilization.…”
Section: A Few Comments About Unique Continuationmentioning
confidence: 99%
“…They have shown that the local energy decays to zero in the sense that, under suitable assumptions, the energy of any solution escapes away from any compact set, see [18], [26] and [2] and the references therein. Secondly, several works have studied the damped wave equation in an unbounded manifold and with a non-linearity, but assuming that the damping satisfies γ(x) ≥ α > 0 outside a compact set, see [33], [10], [9] and [16].…”
Section: Some Previous Workmentioning
confidence: 99%
“…Another related problem is the asymptotic behaviour of the non-linear equation as studied in [33], [10], [9] or [16]. One considers the non-linear equation To each solution of (6.5), one can associate the energy…”
Section: Global Attractor and Stabilisation For The Non-linear Equationmentioning
confidence: 99%
“…We refer to to the linear case and for the case of nonlinearities of order at most p3. The case p[3,5) has been studied by Dehman, Lebeau and Zuazua in and Joly and Laurent in . The critical case p=5 has been investigated in .…”
Section: Introductionmentioning
confidence: 99%